Key factors affecting the integration of interprofessional education into human resources for health reform: a Lao People's Democratic Republic case study. Issue 4 (4th July 2019) - Lee, Bumsuk; Phrasisombath, Ketkesone; Shinozaki, Hiromitsu; Vangkonevilay, Phouthone; Bouphavanh, Ketsomsouk; Prabouasone, Khamphanh; Sounthavong, Outhip; Tokita, Yoshiharu; Makino, Takatoshi; Matsui, Hiroki; Saitoh, Takayuki; Tozato, Fusae; et al.
ABSTRACT: Lao People's Democratic Republic (Lao PDR) with a population of 6.8 million is a low middle-income country in Southeast Asia. Despite economic development, Lao PDR is still characterized by a weak health system. The Ministry of Health has launched health reforms to provide better health services and University of Health Sciences (UHS) plays an essential role in Human Resources for Health (HRH) reform. Especially, the importance of its role in training health professionals from entry-level to continuing education has been increased. In 2016, the UHS embedded an Interprofessional Education (IPE) concept into a pre-qualifying course, in collaboration with the World Health Organization and the Gunma University Centre for Research and Training on IPE. As a pilot study, some students from faculties of Medicine, Pharmacy, Dentistry, Nursing, and Medical Technology participated in a community-based IPE program. Results suggested that students participating in the IPE program showed more positive attitudes toward collaborative practice than students who did not participate in the IPE program. Based on the results, the UHS is planning to develop an IPE program for health workers. In this article, we describe the strategic international collaboration and discuss the keys to successful IPE planning and implementation in line with HRH reform.